Detailed analysis of skull morphology and brain size in crested Padovana chicken (Gallus gallus f.d.) - Wolf-Vollenbröker, Michael; Petow, Stefanie; Schmidbauer, Max; Fellmin, Mareike; Ulrich, Reiner; Mehlhorn, Julia (Frontiers in Ecology and Evolution, 2024)
Crested chicken show abnormalities in their anatomy of the skull, endocranium and brain (including cerebral elongation) and can be appropriate model systems for neuroanatomical evolution, brain-skull integration and skull and brain deformities. Here, we give a detailed comprehensive description of the skull of crested chicken using the example of Padovana chicken, including ontogenetic aspects and an allometric analysis of their brain size. In total, 109 chicken of two different strains of Padovana chicken were hatched together. All animals were x-rayed weekly during growth. Nine juvenile (ready for hatch) and 22 adult skulls were processed for histology and morphological descriptions, further 20 individuals for the brain analysis. At hatching, all chicks were already crested, a distinctive bony protuberance was firstly shown at an age of 4 weeks. Juvenile chicken exhibit either an open neurocranium or a protuberance. In the adult skull, foramina of different sizes can be found in the frontal bone, but no completely open neurocrania as observed in juveniles. Particularly in Padovana with cranial protuberances, several peculiarities can be observed in the Os mesethmoidale, Os nasale, Os praemaxillare, orbit and cranial fossae. Besides, the brain of Padovana with cranial protuberances looks like drawn in length with the shape of an hour-glass and showed significant larger encephalisation indices than plain-headed breeds, topped only by another crested chicken breed. Investigations on chicken with cerebral elongation may facilitate the understanding of skull and brain dysplasia and may provide meaningful insights into cerebral hernia development. Additionally, crested breeds, combined with standard chickens, form a promising comparative system for investigating the emergence of novel brain and skull morphologies.